From contrastive rhetoric towards perceptions of identity: written academic English in Central Mexico - Crawford, Troy; Mora Pablo, Irasema; Lengelign, Martha; Goodwin, Douglas (Colombian Applied Linguistics Journal, 2013)
This research looks at two students at the end of a four year period in academic writing as a second language using open interviews and textual analysis of academic papers. While the initial focus of the research was on the development of rhetorical features in academic texts, issues more oriented to identity construction emerged through the data analysis, implying that long term academic writing in a second language may be more akin to literacy development. The results seem to show that while the participants express a strong identity with English as writers, the actual writing is more in tune with conventions of Spanish. This suggests an apparent conflict of English as a tool for writing and Spanish as the language of the individual.